STUDY OF EFFECTIVITY Bacillus thuringiensis BASED BIO-INSECTICIDE AGAINST Oryctes rhinoceros LARVAE AT SHADE HOUSE - M Ridwan; H Saputra; M Agusrafil; A Nurnabila; Henny Hendarjanti; Yulia Pujiastuti (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
Oryctes rhinoceros is an important pest in oil palm plantations. Adult stage of the beetle causes damage, however larval stage is very important to be controlled to break the cycle of life. An entomopathogenic bacterium Bacillus thuringiensis is one of biological agents to control these insects. Its toxic protein content provides specific insect targets as stomach poison. Objectives of the research was to study the impact of B. thuringiensis propagated in bio-urine enriched with 5 per cent molasses towards Oryctes larvae. The research was carried out in the shade house of Plant Protection Study Program, Faculty of Agriculture, Sriwijaya University from August to November 2021. Experiment was designed in a randomized complete block design with 7 treatments and 4 replications. A total of 20 ml of bio-insecticide was dissolved in 280 ml of water, sprayed evenly on the soil mixed with male palm flowers as feed of larvae. The treatments were 6 isolates of B. thuringiensis isolated from soil in oilpalm plantation, namely with codes: C14, C15, A15, OJ, BK, and LK as well. The results showed density of B. thuringiensis spores in bio-urine media was different in each isolate. The highest spore density in isolate code LK was 4.83 x 1010 spores/ml and the lowest (in isolate A15) was at 3.5 x 1010 spores/ml. Mortality rates were significantly different between isolate treatments starting from day 3 to day 12 of observation. C15 isolate lead the highest mortality rate of 100% on day 12 while other isolates showed mortality data below 100% (88-98%). Body weight and length showed significantly differences on days 0, 6 and 12 after application. Symptoms of infection begin with a change in skin color from white to brown, dark brown and black. Death is characterized by a soft body texture and wet rot.